Aulas em multimídia como ferramenta pedagógica na melhoria do ensino de química de alunos do 1º ano do ensino médio: um estudo de caso. - Oliveira, Carlos Antônio Chaves de (2015)
Many researches have pointed out that the use of information and communication technologies, specifically the use of information technology, is increasingly present in the school environment, assisting in the process of teaching and learning. Whereas the computer and the media in general are part of the daily life of students and today represent an important reference tool and study, the school can not refrain from this reality in their environment. This should therefore assume a role that goes beyond the mere transmission of content accumulated in streams such content, if not streamlined with the daily life of students will not be channeled to the development of skills required for the commitment that education Basic objective to foster in students. In this context, this paper proposes formulate, implement multimedia capabilities and make a research about the influence in order to strengthen the actions of the Chemistry faculty in order to minimize the gaps of traditional education they can not approach the students of science for its abstractness. The survey was conducted in a public school in Fortaleza - CE, located in Ceará Barra neighborhood, chosen by their results against the Basic Education Development Index (IDEB), which was 4.5 for the year 2013. Has herself, initially, a literature review on the use of Information and Communication Technologies (ICT) in teaching Chemistry. In addition to textbooks, other sources were used to prepare the material. Five CDs were prepared, using software like PowerPoint, Prezi, Word, Adobe Flash Player for cooking classes in multimedia. Also made use of video and two simulators. In order to verify the effectiveness of the material produced was selected two groups, one called control and other work to make implementation of the CD corresponding to the 2nd quarter contents, according to the teaching plan. The study was based on a qualitative and quantitative treatment on the acquisition of knowledge about the concepts of atomic structure, electronic distribution, periodic table, periodic properties, atomic and molecular interactions, molecular geometry, polarity connections, intermolecular interactions, sigma bonds and pi , seeking the understanding facilitator way for your event. The results obtained by evaluating the proposed exercises in CDs and collecting opinions showed that all students have an interest in learning the content taught through the use of technological tools is the media type, simulators, exercise bench, internet, finally all set of features that make up the digital universe. The classes in multimedia, containing all the contents of the first year of high school, were the educational product generated in this research. This was made available in the staff room, the official website of the school on the Internet, as support material, and computer labs, that they may serve as a research and review source for students.